2002
DOI: 10.1021/ja026317b
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Intramolecular Oxidative Alkylation of Unactivated Olefins

Abstract: Reaction of 5,5-dimethyl-8-nonene-2,4-dione catalyzed by PdCl2(CH3CN)2 (5 mol %) in the presence of CuCl2 (2.5 equiv) at room temperature for 3 h formed 2-acetyl-3,6,6-trimethyl-2-cyclohexenone in 96% isolated yield. Palladium-catalyzed intramolecular oxidative alkylation tolerated a range of substitution and was applicable to the synthesis of spirobicyclic compounds and to the cyclization of zeta-alkenyl beta-keto esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…
Biomimetic polyolefin cascade reactions [1,2] represent some of the most challenging problems in reaction design, and their products are ubiquitous in the natural world.[3] Since the Brønsted-Lewis acids (BLAs) of Yamamoto et al are the only known synthetic catalysts for asymmetric catalytic initiation of cation-olefin cyclizations, [4,5] [7] and Toyota, Ihara et al [8] demonstrated that nucleophilic enols lead to carbocyclic products by b-hydride elimination [9] or protonation. [10] Although substituent effects [11] and stereochemical studies [6c] support a cationic and cyclic intermediate, respectively, the exact nature of this intermediate is unclear, and direct evidence for this cation is lacking.

[12] We therefore initiated a plan that first gathered evidence supporting the intermediacy of the carbocyclic cation, while also determining whether it could function as a point for initiating new metal-mediated reactivity.

…”
mentioning
confidence: 99%
“…
Biomimetic polyolefin cascade reactions [1,2] represent some of the most challenging problems in reaction design, and their products are ubiquitous in the natural world.[3] Since the Brønsted-Lewis acids (BLAs) of Yamamoto et al are the only known synthetic catalysts for asymmetric catalytic initiation of cation-olefin cyclizations, [4,5] [7] and Toyota, Ihara et al [8] demonstrated that nucleophilic enols lead to carbocyclic products by b-hydride elimination [9] or protonation. [10] Although substituent effects [11] and stereochemical studies [6c] support a cationic and cyclic intermediate, respectively, the exact nature of this intermediate is unclear, and direct evidence for this cation is lacking.

[12] We therefore initiated a plan that first gathered evidence supporting the intermediacy of the carbocyclic cation, while also determining whether it could function as a point for initiating new metal-mediated reactivity.

…”
mentioning
confidence: 99%
“…In contrast, 4-pentenyl β-diketones and some 4-pentenyl β-keto esters underwent selective oxidative alkylation in the presence of 2 to form cyclohexenone derivatives in good yield with good regioselectivity [15]. For example, treatment of 8-nonene-2,4-dione (4) with a stoichiometric amount of 2 in dioxane at room temperature for 15 min led to isolation of an ~8:1 mixture of cyclohexenone 5 and cyclohexanone 6 in 85 % combined yield (eq.…”
Section: Oxidative Alkylation Of 4-pentenyl ␤-Dicarbonyl Compoundsmentioning
confidence: 99%
“…In accord with our initial expectations, 4 tolerated the conditions required for in situ oxidation of Pd(0) to Pd(II) and reaction of 4 with a catalytic amount of 2 (5 mol %) and CuCl 2 (2.5 equiv) at room temperature for 3 h led to the isolation of 5 in 80 % yield (Scheme 3). Oxidative alkylation of 4 was also achieved employing a catalytic amount of both 2 (5 mol %) and CuCl 2 (10 mol %) under an oxygen atmosphere to give 5 in 70 % isolated yield (Scheme 3) [15]. Palladium-catalyzed oxidative alkylation of 4-pentyl β-diketones tolerated substitution at the terminal acyl carbon, and along the 4-pentenyl chain (Table 2).…”
Section: Oxidative Alkylation Of 4-pentenyl ␤-Dicarbonyl Compoundsmentioning
confidence: 99%
“…(2)]. [3,4] As an example, reaction of 8-nonene-2,4-dione with a catalytic amount of 2 (5 mol %) and a stoichiometric amount of CuCl 2 in dioxane at room temperature for 3 h led to isolation of 2-acetyl-3-methyl-2-cyclohexenone in 80 % yield [Eq. (2)].…”
Section: Introductionmentioning
confidence: 99%
“…(2)]. [3,4] On the basis of deuterium-labeling, kinetic, and in situ NMR experiments, we have proposed a mechanism for the palladium-catalyzed hydroalkylation of 1 involving attack of the pendant enol on the palladium-complexed olefin of I to form the palladium-cyclohexyl species II (Scheme 1). [2,4,5] Isomerization of II through iterative b-hydride elimination/ addition followed by protonolysis of the palladium-enolate species III forms 3 with regeneration of 2 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%